Phylogeny and Divergence Times of Gymnosperms Inferred from Single-Copy Nuclear Genes - Lu, Ying; Ran, Jin-Hua; Guo, Dong-Mei; Yang, Zu-Yu; Wang, Xiao-Quan (PLOS ONE, 2014)
Phylogenetic reconstruction is fundamental to study evolutionary biology and historical biogeography. However, there was not a molecular phylogeny of gymnosperms represented by extensive sampling at the genus level, and most published phylogenies of this group were constructed based on cytoplasmic DNA markers and/or the multi-copy nuclear ribosomal DNA. In this study, we use LFY and NLY, two single-copy nuclear genes that originated from an ancient gene duplication in the ancestor of seed plants, to reconstruct the phylogeny and estimate divergence times of gymnosperms based on a complete sampling of extant genera. The results indicate that the combined LFY and NLY coding sequences can resolve interfamilial relationships of gymnosperms and intergeneric relationships of most families. Moreover, the addition of intron sequences can improve the resolution in Podocarpaceae but not in cycads, although divergence times of the cycad genera are similar to or longer than those of the Podocarpaceae genera. Our study strongly supports cycads as the basal-most lineage of gymnosperms rather than sister to Ginkgoaceae, and a sister relationship between Podocarpaceae and Araucariaceae and between Cephalotaxaceae-Taxaceae and Cupressaceae. In addition, intergeneric relationships of some families that were controversial, and the relationships between Taxaceae and Cephalotaxaceae and between conifers and Gnetales are discussed based on the nuclear gene evidence. The molecular dating analysis suggests that drastic extinctions occurred in the early evolution of gymnosperms, and extant coniferous genera in the Northern Hemisphere are older than those in the Southern Hemisphere on average. This study provides an evolutionary framework for future studies on gymnosperms.